Encuentros y desencuentros pedagógicos en la educación artística - Fernàndez-Inglés, Soledad (Studi sulla Formazione/Open Journal of Education, 2017)
The present work analyses the effort made by different National and international Organizations united in the common front for the artistic improvement, its pro-gress and repercussions on the teaching of the different levels of education. For many decades, the European Parliament works in the context of the educational action raising the values ‘flag like peace, harmony and tolerance to make it to a fairest society. The Parliament considers that the artistic education is a good path as a social inclusion’s accelerator and a instrument supplier necessary to work on otherness, since increases creativity and, with that, the acquisition of abilities to innovation, very important for the European Union’s competitiveness and devel-opment. Although Institutions and different Organizations have been providing many recommendations since the eighties of last century, the teaching field has barely transformed due to its complexity. It is intuited that this type of teaching promotes creativity, critical thinking and social and behavioral abilities, but what syllabus does the formal education need to follow and what pedagogical resources have to be adopted in order to develop these abilities? Maybe the answer comes from the visual culture field, but for this the future teaching education has to be of quality, as well as continued in time.